2019
DOI: 10.1186/s41232-019-0097-x
|View full text |Cite
|
Sign up to set email alerts
|

Calendula officinalis stimulate proliferation of mouse embryonic fibroblasts via expression of growth factors TGFβ1 and bFGF

Abstract: Background TGF-β has an important role in the process of wound healing and scar formation. The aim of this study is to determine the effects of ethanolic and methanolic extracts of Calendula officinalis on the expression of TGFβ1 and bFGF in the mouse embryonic fibroblast cells (MEFs). Methods Calendula officinalis extract was purchased and different substances defined with gas chromatography and mass spectrometry. MEFs were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 21 publications
0
7
0
1
Order By: Relevance
“…On the other hand, a diet containing vegetables and fruit can protect against colorectal cancer, due to its richness in fiber and such nutrients as calcium, selenium, vitamins A, E, C, and D, folic acid, carotenoids, and plant phenols. 4,5 Hydroxytyrosol is one of the most potent antioxidant phenolic compounds in olives, and is able to transfer the hydroxyl electron group to its ortho position and form a hydrogen-bonding molecule with radical phenoxylic stability. 6,7 Research has shown that the incidence of cancer in the Mediterranean region is lower than in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, a diet containing vegetables and fruit can protect against colorectal cancer, due to its richness in fiber and such nutrients as calcium, selenium, vitamins A, E, C, and D, folic acid, carotenoids, and plant phenols. 4,5 Hydroxytyrosol is one of the most potent antioxidant phenolic compounds in olives, and is able to transfer the hydroxyl electron group to its ortho position and form a hydrogen-bonding molecule with radical phenoxylic stability. 6,7 Research has shown that the incidence of cancer in the Mediterranean region is lower than in other countries.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Hormozi et al examined the wound healing effect of C. officinalis extract administered at the following concentrations: 5, 10, 20, 40, and 50 µg mL −1 . Their studies confirmed that concentrations of 5 μg mL −1 and 10 μg mL −1 were more suitable for cell proliferation of fibroblasts [ 23 ]. Moreover, Fronza et al showed that both hexane and ethanolic extracts from C. officinalis stimulated proliferation and migration of fibroblasts at low concentrations (i.e., 1 and 10 µg mL −1 ) [ 22 ].…”
Section: Resultsmentioning
confidence: 85%
“…After 12 h and 24 h of the treatment, a significant increase the wound-healing rate by 31%, 34%, and 33% and 68%, 68%, and 69% was observed for concentrations of 31.25, 62.5, and 125.0 µg mL −1 respectively, compared to the untreated control (23% and 46%). The highest concentration (250 µg mL −1 ) demonstrated the weakest effect on the migration of fibroblasts, and increasing the wound healing was 29% after 12 h and 55% after 24 h. Their studies confirmed that concentrations of 5 µg mL −1 and 10 µg mL −1 were more suitable for cell proliferation of fibroblasts [23]. Moreover, Fronza et al showed that both hexane and ethanolic extracts from C. officinalis stimulated proliferation and migration of fibroblasts at low concentrations (i.e., 1 and 10 µg mL −1 ) [22].…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations